Assessment of Environmental and Social Effects of Rural Toilet Retrofitting on a Regional Scale in China - Gao, Yi; Tan, Lu; Zhang, Chunxue; Li, Qian; Wei, Xiaocheng; Yang, Bo; Chen, Peizhen; Zheng, Xiangqun; Xu, Yan (Frontiers in Environmental Science, 2022)
In China, more than 47 million toilets in rural areas have been upgraded since the nationwide sanitation program, popularly referred to as the “toilet revolution”, was launched in 2015. However, little is currently known about the environmental risks of manure, or about rural residents’ satisfaction. Here, we have selected 50 rural residents from 10 provinces, and focus on two types of toilets, to evaluate the environmental and social impacts of improving toilets in rural areas. The monitoring results showed that human excrement was mainly alkaline, and the concentrations of total nitrogen and phosphorus in the composting toilets ranged from 259.21 to 330.46 mg/kg, and from 2.71 to 3.71 mg/kg, respectively, while their contents in septic tank effluents were generally 381.31-2040.84 mg/L and 10.41-80.46 mg/L, respectively. The pH and EC values exceeded the soil background value in individual regions, and the harmless effect of the two types of toilets did not fully meet the standard requirements, indicating that toilet manure albeit possessed a certain resource utilization potential, yet guard against the risk of pollution. Additionally, based on a fuzzy comprehensive evaluation model, it was found that the comprehensive evaluation score of Jiangsu Province is the highest, that of Gansu Province is the lowest, and the overall score is “high in the southeast and low in the northwest”. This study provides basic data and references for establishing a scientific and feasible evaluation system of rural toilet retrofitting, and strengthens government guidance and training related to toilet retrofitting.